Workshop Pengenalan Aplikasi Pembelajaran Diffit bagi Guru untuk Menunjang Pembelajaran Era Digital di SMAN 2 Nekamese - A. Pekuwali, Dian Sari; Labu Djuli; Narantoputrayadi Makan Malay; Tince Taela M. Nenoliu; Paulina Y. Kosat (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2025)
Recognizing the demands of adapting to technology in the digital era, this Community Service Program (PKM) targets teachers at SMA Negeri 2 Nekamese who still face challenges in utilizing innovative applications to improve administrative efficiency and learning quality. Improving teachers' digital competency is necessary to create relevant and engaging learning experiences. Solutions are provided through workshops and hands-on mentoring focused on utilizing the Artificial Intelligence (AI)-based application, Diffit. Teachers are intensively trained to master Diffit's various features, ensuring the intelligent integration of technology as a pedagogical tool. This activity has significantly improved teacher competency. Teachers are now proficient in using Diffit to transform complex material into various differentiated learning formats (such as summaries and adaptive questions). This drastically reduced the administrative burden and encouraged the implementation of personalized learning (deep learning) in the classroom. This success serves as a model for good practice in empowering teachers through AI. This PkM also strengthens Undana's Tri Dharma by providing a basis for empirical validation for lecturers and real-world experience (experiential learning) that strengthens students' Edutech profiles. This PkM successfully transformed teachers' teaching practices, so it is recommended that schools institutionalize the use of Diffit, and Undana publish this training model for sustainability.